2012
DOI: 10.1007/s00104-011-2182-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiologische Diagnostik der intraduktalen papillär muzinösen Neoplasie

Abstract: The intraductal papillary mucinous neoplasm (IPMN) is the most frequent cystic neoplasm of the pancreas. Due to the widespread use of cross-sectional imaging IPMN is being incidentally recognized with increasing frequency. The most common type is branch- duct IPMN which occurs multifocally in about 20-30%. Patients with IPMN may present with symptoms resembling chronic pancreatitis and episodes of acute pancreatitis are increasingly being reported which usually have a mild course. The most important diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Interestingly, in our series, bile duct obstruction is only seen in the invasive group, with all the tumors located in the pancreatic head. This finding is supported by Brambs et al [27, 28] as well as Ogawa et al [29]; both judged biliary obstruction to be an index for the malignancy of an IPMN lesion [20]. …”
Section: Discussionmentioning
confidence: 57%
“…Interestingly, in our series, bile duct obstruction is only seen in the invasive group, with all the tumors located in the pancreatic head. This finding is supported by Brambs et al [27, 28] as well as Ogawa et al [29]; both judged biliary obstruction to be an index for the malignancy of an IPMN lesion [20]. …”
Section: Discussionmentioning
confidence: 57%
“…Previous studies have suggested a number of individual criteria to predict malignancy in pancreatic IPMN [6,[14][15][16] . The summation score suggested here was based on the evaluation of these parameters as well as the determination of the CT density of the lesions.…”
Section: Discussionmentioning
confidence: 99%